2020
DOI: 10.3390/cancers12010130
|View full text |Cite
|
Sign up to set email alerts
|

In the Absence of a TCR Signal IL-2/IL-12/18-Stimulated γδ T Cells Demonstrate Potent Anti-Tumoral Function Through Direct Killing and Senescence Induction in Cancer Cells

Abstract: Abundant IFN-γ secretion, potent cytotoxicity, and major histocompatibility complex-independent targeting of a large spectrum of tumors make γδ T cells attractive candidates for cancer immunotherapy. Upon tumor recognition through the T-cell receptor (TCR), NK-receptors, or NKG2D, γδ T cells generate the pro-inflammatory cytokines TNF-α and IFN-γ, or granzymes and perforin that mediate cellular apoptosis. Despite these favorable potentials, most clinical trials testing the adoptive transfer of pharmacologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The synergistic function of IL-12 and IL-18 in inducing the IFN-γ production of T cells and NK cells has been demonstrated ( 96 – 99 ). Similarly, IL-12 and IL-18 also induced the production of IFN-γ and increased cytotoxicity in γδT cells in an antigen-independent manner ( Figure 3 ) ( 100 , 101 ). However, the combination of IL-12 and IL-18 led to the upregulation of TIM3 on γδT cells ( 102 ).…”
Section: Cytokine-mediated Regulation Of γδT Cell Functionmentioning
confidence: 86%
“…The synergistic function of IL-12 and IL-18 in inducing the IFN-γ production of T cells and NK cells has been demonstrated ( 96 – 99 ). Similarly, IL-12 and IL-18 also induced the production of IFN-γ and increased cytotoxicity in γδT cells in an antigen-independent manner ( Figure 3 ) ( 100 , 101 ). However, the combination of IL-12 and IL-18 led to the upregulation of TIM3 on γδT cells ( 102 ).…”
Section: Cytokine-mediated Regulation Of γδT Cell Functionmentioning
confidence: 86%
“…Therefore, CIS can result from novel therapeutic approaches that link, for instance, radiotherapy to an otherwise sole but still efficient immunotherapy [108]. In the context of cell-based immunotherapy, it was also recently shown that gamma delta (γδ) T cells bear a promising anti-tumor activity [109]. The study demonstrated that the TCR-independent stimulation of γδ T cells with cytokines such as IL-2, IL-12, and IL-18 enhanced their anti-tumoral potential.…”
Section: Cytokine-induced Senescence (Cis)mentioning
confidence: 99%
“…The study demonstrated that the TCR-independent stimulation of γδ T cells with cytokines such as IL-2, IL-12, and IL-18 enhanced their anti-tumoral potential. This is achieved as γδ T cells do not only induce apoptosis through cytotoxic factors such as granzymes or perforin, but also tumor cell senescence through the production of IFN-γ and TNF [109].…”
Section: Cytokine-induced Senescence (Cis)mentioning
confidence: 99%
See 1 more Smart Citation
“…5,23,[26][27][28] On the other hand, in vitro experiments and in vivo NHP studies have well established that Vγ2Vδ2 T cells, once activated by IPP or HMBPP, can be readily expanded by IL-2, IL-7, IL-15, IL-21, IL-33, and Th17-related cytokines. 17,26,[29][30][31] In fact, recent seminal studies in NHP models suggest that the phosphoantigen HMBPP-specific Vγ2Vδ2 T-cell subpopulation can respond as fast-acting T cells during microbial infections. 3,5,23 During primary microbial infections of NHPs mimicking human TB and other pathogens,…”
Section: Il-12 S I G Naling Pathway Drive S E Arly De Velopment Of mentioning
confidence: 99%